Financial Performance Bank BNI Syariah Company - Rachmawati, Diana Widhi (Universitas Islam Negeri Raden Intan Lampung, 2018)
ABSTRACTPT Bank BNI Syariah, one of them working are a big banking company is almost covering all over the country until now looked at pretty good company asset which are owned, so author conduct research in the title “Financial Performance PT Bank BNI Syariah in Solvability Ratio”. Financial Statement Analysis is aplication from tools and technical analysis financial report general aim and data to be related and estimation produce useful conclutions in business analysis. Financial Performance Analysis research used analysis methode is solvability ratio. General aim to give information finance performance PT Bank BNI Syariah development. Special goals is finance performance PT Bank BNI Syariah from Solvability Ratio”. This Sample is: PT Bank BNI Syariah. Final result which is research obtained it says finance performance PT Bank BNI Syariah from Solvability Ratio quite solvable, because this three point inside it contained increased. This development hope PT Bank BNI Syariah, to be remain consistent with trying to do breakthrough a company goals Key Words : Financial Performance PT Bank BNI Syariah